Improving Tenth Grade Students' English Recount Text Writing Skills through Interactive Tasks - Oinuma, Sachi (STAIN Majene, 2024)
This study investigates the effectiveness of innovative methods to enhance tenth grade students’ English writing proficiency at SMK IPTEK Weru Sukoharjo, focusing on recount text. Using Classroom Action Research (CAR), the study employed both qualitative and quantitative approaches, including observations, interviews, and pre-test and post-test. The findings indicate that interactive and collaborative writing exercises, supported by multimedia resources and constructive feedback, significantly improved students’ writing skills and engagement. However, the challenges using vocabulary and organizing recount narratives highlights areas for further pedagogical improvement. The study underscores the importance of dynamic, student-centered English writing instruction tailored to vocational education to better prepare students for future academic and professional pursuits.